Sustainable development indicators and possibilities of their mapping - Popovych, Nataliia (Проблеми безперервної географічної освіти і картографії)
The article deals with the sets of sustainable development indicators and sustainable development indexes. Among approaches used in indicators design the author has identified geosystemic, target, problematic, sectoral and functional ones. It is denoted that the most widely used indicator sets are the OECD programme on ecological indicators and the system of indicators created by the UNO Division for Sustainable Development. The author analyzes the integral indexes of sustainable development, such as Living Planet Index, Human Development Index, Human Poverty Index, Adjusted Net Savings and the Ecological Footprint. It is emphasized that integral indicators and indexes are rarely used in sustainable development strategies (the reason for this could be some methodological limitations or lack of statistical data). The analysis of national sustainable development strategies of European countries has showed that the target approach is mainly used in the development of indicators and their number vary from 32 (Estonia) to 610 (Latvia). Sustainable development strategies indicators are expressed in the text and table forms; charts and graphs are commonly used in the monitoring reports, whereas cartographic works are hardly represented. The author has presented the following key recommendations for mapping indicators for sustainable development strategies: to use component system of indicators as the basis for integral indicators design; to use either territory or population as a «common denominator » for indicators; to give users the most complete picture of the territory development applying the least possible number of maps; to use collation and diagram maps which are the most appropriate way of cartographic representation.